Optimization of Dual-Labeled Antibodies for Targeted Intraoperative Imaging of Tumors - Mark Rijpkema; Desirée L. Bos; Alex S. Cornelissen; Gerben M. Franssen; David M. Goldenberg; Wim J. Oyen; Otto C. Boerman (Molecular Imaging)
For intraoperative imaging, antibodies labeled with both a radionuclide and a fluorophore may be used to tag the tumor lesion with a radiolabel and a fluorescent signal at high tumor to background ratios. However, labeling antibodies with fluorescent moieties may affect the in vivo behavior of the antibody depending on the dye to antibody substitution ratio. To investigate the optimal substitution ratio for use in dual-modality image-guided surgery, we conjugated three different antibodies, MN-14 (anti-CEACAM5), girentuximab (anti-CAIX), and cetuximab (anti-EGFR), with both diethylene triamine pentaacetic acid (DTPA, for labeling with 111 In) and IRdye 800CW at dye to antibody ratios of 0, 1, 1.5, 2, and 3 and assessed in vivo behavior. Biodistribution studies showed that at high dye to antibody ratios, liver uptake of the dual-labeled antibodies increased, whereas tumor uptake decreased. Conversely, very low ratios may not be optimal either because in that case, only a few antibody molecules will be dual-labeled (i.e., contain both a DTPA and an IRDye 800CW moiety), which may complicate interpretation of dual-modality data. The present study shows that, provided that the chelator to antibody ratio is high enough, a dye to antibody ratio in the range of 1 to 1.5 is optimal for antibody-targeted dual-modality imaging applications. However, the optimal configuration is antibody dependent and should be determined for each dual-labeled antibody individually.